2017
DOI: 10.1096/fj.201600985r
|View full text |Cite|
|
Sign up to set email alerts
|

Hepatic DsbA‐L protects mice from diet‐induced hepatosteatosis and insulin resistance

Abstract: Hepatic insulin resistance and hepatosteatosis in diet-induced obesity are associated with various metabolic diseases, yet the underlying mechanisms remain to be fully elucidated. Here we show that the expression levels of the disulfide-bond A oxidoreductase-like protein (DsbA-L) are significantly reduced in the liver of obese mice and humans. Liver-specific knockout or adenovirus-mediated overexpression of DsbA-L exacerbates or alleviates, respectively, high-fat diet-induced mitochondrial dysfunction, hepatos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…have shown that aberrant activation of the cGAS–STING–IFN-I pathway exacerbates obesity-induced inflammation and insulin resistance [35]. Genetic ablation of Dsba-L, a protein chaperone localized to the mitochondrial matrix, enhanced mtDNA leakage and cGAS–STING activation in adipocytes, while over-expression protected against inflammatory responses and liver damage in obese mice [35,36]. Myocardial infarction also drives a classical IFN-I response downstream of cGAS–STING activation [37].…”
Section: Dna Sensing During Inflammationmentioning
confidence: 99%
“…have shown that aberrant activation of the cGAS–STING–IFN-I pathway exacerbates obesity-induced inflammation and insulin resistance [35]. Genetic ablation of Dsba-L, a protein chaperone localized to the mitochondrial matrix, enhanced mtDNA leakage and cGAS–STING activation in adipocytes, while over-expression protected against inflammatory responses and liver damage in obese mice [35,36]. Myocardial infarction also drives a classical IFN-I response downstream of cGAS–STING activation [37].…”
Section: Dna Sensing During Inflammationmentioning
confidence: 99%
“…Chen et al . showed that hepatic DsbA‐L protects mice from high‐fat diet‐induced fatty liver and insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…14 In addition, it has been reported that the mRNA level of DsbA-L in adipose tissue correlated negatively with obesity in both mice and humans. 13,14 Chen et al 16 showed that the liver-specific knock-out of DsbA-L in mice exacerbated high-fat diet-induced hepatosteatosis, and the overexpression of DsbA-L protected mice against hepatosteatosis and insulin resistance. Furthermore, the suppression of DsbA-L is associated with the impairment of the respiratory capacity in mitochondria and the elevation of cellular oxidative stress.…”
Section: What Does This Study Add To Our Knowledge?mentioning
confidence: 99%
See 2 more Smart Citations